Rare bird documentation form for Northern Goshawk at Lakin's Slough, 1981 - Cummins, Raymond L.et al (1981)
Rare bird documentation form for a Northern Goshawk at Lakin's Slough at Guthrie County, IA on December 23, 1981. Epson - sheet feed